Multiscale simulation of the interlaminar failure of graphene nanoplatelets reinforced fibers laminate composite materials. Issue 25 (22nd February 2019) - Basso, Matteo; Azoti, Wiyao; Elmarakbi, Hana; Elmarakbi, Ahmed
ABSTRACT: This article presents a multiscale approach to derive the interlaminar properties of graphene nanoplatelets (GNPs)‐based polymeric composites reinforced by short glass fibers (SGFs) and unidirectional carbon fibers (UCFs). The approach accounts for the debonding at the interface of a 2‐phases GNPs/polymer matrix using a cohesive model. The resulting composite is used within a 3‐phases nanocomposite consisting either of a GNPs/polyamide/SGFs or a GNPs/epoxy/UCFs nanocomposite. Experiments are performed for determining the interlaminar fracture toughness in mode I for the GNPs/epoxy/UCFs. Results show that the aspect ratio (AR) of GNPs influences the effective Young modulus which increases until a threshold. Also, the addition of the GNPs increases up to 10% the transverse Young modulus and up to 11% the shear modulus as well as up to 16% the transverse tensile strength useful in crashworthiness performance. However, the nanocomposite behavior remains fiber dominant in the longitudinal direction. This leads to a weak variation of the mechanical properties in that direction. Due to the well‐known uniform dispersion issues of GNPs, the interlaminar fracture toughness GIC has decreased up to 8.5% for simulation and up to 2.4% for experiments while no significant variation of the interlaminar stress distribution is obtained compared to a nanocomposite without GNPs. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47664. Abstract :